The equation above is true for some positive integer . Find .
Clarification: denotes the Euler's number .
The problem is original
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a + b i = a 2 + b 2 e i tan − 1 a b Similarly lo g ( a + b i ) = lo g ( a 2 + b 2 ) + i tan − 1 ( a b ) lo g ( 1 + a e i x ) = lo g ( ( 1 + a cos ( x ) ) 2 + a 2 sin 2 ( x ) ) + i tan − 1 ( a cos ( x ) + 1 a sin ( x ) ) lo g ( 1 + a e i x ) = ( a cos ( x ) − 2 a 2 cos ( 2 x ) + 3 a 3 cos ( 3 x ) − ⋯ ) + i ( a sin ( x ) − 2 a 2 sin ( 2 x ) + 3 a 3 sin ( 3 x ) − ⋯ Matching both sides we get tan − 1 ( a cos ( x ) + 1 a sin ( x ) ) = a sin ( x ) − 2 a 2 sin ( 2 x ) + 3 a 3 sin ( 3 x ) − ⋯ Take a = e 1
e sin ( 1 ) − 2 e 2 sin ( 2 ) + 3 e 3 sin ( 3 ) − 4 e 4 sin ( 4 ) + ⋯ = tan − 1 ( cos ( 1 ) + e sin ( 1 ) ) Answer is a = 1